EVALUASI PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L.) PADA 2 MACAM DESAIN GREENHOUSE UNISBA BLITAR - Melina Savitri, Olivia; Puspitorini, Palupi; Dita Serdani, Army; Pitaloka, Dyah (grafting, 2023)
The aim of the research is to determine the effect of differences in melon cultivation in two greenhouse construction designs which provide the best results on the growth and yield of melon plants (Cucumis melo L.). The research was conducted from July to September 2022 at the Balitar Islamic University of Blitar Greenhouse. The design used is a dependent analysis method which tests the relationship between independent variables. The analysis technique used is the parametric t-test. The t-test difference test was carried out on two category groups with the condition of two paired sample groups (paired sample t-test). The variables observed were plant height (cm), number of side shoots (strands), stem diameter (cm) and fresh fruit weight (gr). The results showed that the Greenhouse 1 (GH1) design provided an agro-climatic environment that was more in line with the environment needed by the melon plants significantly compared to the GH2 design so as to provide better melon plant growth and better yields. The average fruit fresh weight for melon plants cultivated in GH1 was 1008.52 grams of side shoots which was significantly better than in GH2 which was 968.32 grams.